2015
DOI: 10.1007/s12192-014-0532-5
|View full text |Cite
|
Sign up to set email alerts
|

A hypoxia-induced decrease of either MICA/B or Hsp70 on the membrane of tumor cells mediates immune escape from NK cells

Abstract: Recent findings suggest that hypoxia of the tumor microenvironment contributes to immune escape from natural killer (NK) cell-mediated cytotoxicity. Heat shock protein 70 (Hsp70) and the stress-regulated major histocompatibility class I chain-related protein A and B (MICA/B) both serve as ligands for activated NK cells when expressed on the cell surface of tumor cells. Herein, we studied the effects of hypoxia and hypoxia-inducible factor-1α (HIF-1α) on the membrane expression of these NK cell ligands in H1339… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…HIF1A in lung cancer cells with high basal HIF1A levels [27]. In our previous study, we also demonstrated that after hypoxia-induced HIF1A upregulation and consequent sMICA upregulation, NKG2D is decreasingly located at the membrane and is increasingly present in the cytoplasm following binding to sMICA [9].…”
Section: Discussionmentioning
confidence: 71%
“…HIF1A in lung cancer cells with high basal HIF1A levels [27]. In our previous study, we also demonstrated that after hypoxia-induced HIF1A upregulation and consequent sMICA upregulation, NKG2D is decreasingly located at the membrane and is increasingly present in the cytoplasm following binding to sMICA [9].…”
Section: Discussionmentioning
confidence: 71%
“…HSP6A encodes heat-shock protein 70, which is a stress-induced protein like MICB. Both are ligands of activating receptors in NK cells, and their increased expressions are associated with missing self recognition by NK cells (20) and activation of NK cells. PYK2 is a downstream molecule of activatory and inhibitory receptors in NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal circumstances, HSP70 expression is relatively low; however, under the conditions of protein damage caused by heat shock and hypoxia, HSP70 protein may be regulated by the PI3K/AKT/NRF2 pathway, and its expression is increased [36,37]. A previous study has shown that HSP70 plays a synergistic role with immune cells in antitumor immunity [38]. Moreover, heat shock factor 1 (HSF-1), one of the best known activators of HSP70 expression, is also an activator of the MICA gene promoter [39].…”
Section: Metformin Upregulates Mica and Hsp70 Expression To Increase mentioning
confidence: 99%